A comparative evaluation of the reliability of three methods of assessing gingival biotype in dentate subjects in different age groups: An in vivo study - Sarfaraz Memon; Jayanti R Patel; Rajesh Sethuraman; Ravi Patel; Himanshu Arora (Wolters Kluwer Medknow Publications, 2015)
Introduction: In the modern competitive society, a pleasing appearance often dictates the difference between success and failure in both our personal and professional lives. Evaluation of gingival biotype is very important from the start of treatment plan to the final restorative placement to provide excellent esthetics. Materials and Methodology: For the study, subjects were divided into 4 groups of different ages, from 20-30, 31-40, 41-50 and 51-60 years. 30 subjects (15 men and 15 women) were selected in each group for the study. Examination of the thickness of Gingival Biotype was done in 3 different ways; - Direct visual, William's Graduated Probe and Using modified wax caliper. Results: The McNemar test showed statistically significant differences in the way gingival biotype was identified when comparing visual assessment with assessment using direct measurement (P < 0.001). And there was no statistically significant difference when assessment using a periodontal probe was compared to direct measurement (P < 0.676). There is no correlation for the Biotype among the different age groups. Conclusion: Gingival biotype identification by visual assessment is statistically significantly different from assessment with direct measurement. Gingival biotype identification by assessment with a periodontal probe is not statistically significantly different from direct measurement.